حقيقة الوقف المؤقت وحكمه ومصالحه = The nature of temporary Waqf, its ruling and public interest - Ab Rahman, Muhamad Firdaus; Amanullah, Muhammad (Universiti Sultan Azlan Shah, 2017)
waqf can be made temporary or it is limited to perpetuity. The objectives of this paper are: to critically examine the concept of temporary waqf, to assess the different opinions of the scholars on the issue of temporary waqf and to discuss the evidences relied upon every doctrine, to explore the public interest (maslahah) of contemporary application. A qualitative methodology was employed to analyse the data through inductive and deductive methods. The inductive and deductive methods were used to research the main sources of literatures and to analyse the issues related to the temporary waqf. The findings have shown that an essential features of waqf is not limited only to perpetuity, hence some jurists such as Maliki school of Islami law approves the application of temporary and perpetual waqf. Thus, there is a need for temporary waqf to be enacted and applied as it provides the best interests of donors, beneficiaries and community at large. Impliedly, Islamic legal pronouncements (fatwa’s) which were issued by the State Fatwa Committee in Malaysia should not be limited to the view of a single school of Islamic law, especially in the field of waqf.